employee productivity correlation: work-life balance - Sasando, Adam; Darmastuti, Ismi (LPPM Universitas Duta Bangsa Surakarta, 2025)
This study aims to analyze the effect of work-life balance on employee retention and job satisfaction. The work-life balance phenomenon is increasingly important in the modern era because individuals are required to be able to balance the demands of work and personal life. This study used a quantitative method with an associative approach, involving 196 respondents determined using the Lameshow formula. The research instrument was tested for validity and reliability using SmartPLS 3.2.9 through convergent validity, composite reliability, Cronbach's alpha, and AVE values. The results of the analysis showed that work-life balance has a positive and significant effect on employee retention with a T-statistic value of 21.024 (p < 0.005), and a positive and significant effect on job satisfaction with a T-statistic value of 26.903 (p < 0.005). These findings confirm that employees who are able to manage work-life balance tend to have higher job satisfaction and greater commitment to the organization. Therefore, management strategies that support work-life balance can be an important effort in improving employee performance and loyalty.